Gendered-practices of parents of 1 to 3 year old children - Montaña, Isabela Dominique C. (College of Home Economics, University of the Philippines Diliman, 2020)
This is a study on the gendered-practices of parents of one to three year old children, focusing on parents' perception on the concepts of sex and gender, their descriptions of gendered-practices, and their motivations behind the gendered-practices they do for and with their children. It tackles topics on gendering, feminity and masculinity and the different ways they affect parents' decision and expectations for their children, encouraging and discouraging traditionally gendered-stereotyped materials, behaviors, standards, and ideas, the gender-binary phenomenon, and gender socialization. It also takes into account the current trends on gender perceptions and the different influences on the perceptions towards sex and gender. Furthermore, this study discusses the widespread assumption that a child's gender coincides with their sex and the significant role of parents in children's gender identity development across the lifespan. The research is qualitative in nature and, following a descriptive design, it intended to interview 24 parents - 12 mothers and 12 fathers - of children ages one to three years old, enrolled in laboratory school in Quezon City. The age range was chosen because according to studies, this is the stage wherein children's concepts about gender are quite flexible. The researcher would have examined the data through thematic analysis, guided by the conceptual framework and the related relevant theories, particularly the Sociocultural Theory and the Symbolic Interaction Theory that looks into the relation between human beings and their environment, and the natural and symbolic environmen